2007
DOI: 10.1021/bi061827u
|View full text |Cite
|
Sign up to set email alerts
|

Denaturation of Protein by Chlorine Dioxide:  Oxidative Modification of Tryptophan and Tyrosine Residues

Abstract: Oxychlorine compounds, such as hypochlorous acid (HOCl) and chlorine dioxide (ClO2), have potent antimicrobial activity. Although the biochemical mechanism of the antimicrobial activity of HOCl has been extensively investigated, little is known about that of ClO2. Using bovine serum albumin and glucose-6-phosphate dehydrogenase of Saccharomyces cerevisiae as model proteins, here I demonstrate that the antimicrobial activity of ClO2 is attributable primarily to its protein-denaturing activity. By solubility ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 52 publications
3
69
0
6
Order By: Relevance
“…The antimicrobial activity of CD gas is due to protein denaturation, some of which may be important for spore viability and/or integrity (12,16,24). Recently, Ogata and Shibata (17) demonstrated model peptide denaturation (derived from influenza A virus) via modification of tyrosine and tryptophan residues.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of CD gas is due to protein denaturation, some of which may be important for spore viability and/or integrity (12,16,24). Recently, Ogata and Shibata (17) demonstrated model peptide denaturation (derived from influenza A virus) via modification of tyrosine and tryptophan residues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NaClO is easily inactivated in the presence of biological materials such as blood cells and plasma proteins. In comparison, chlorine dioxide (ClO 2 ) is a water-soluble and yellow gas with a strong oxidizing activity (5,6). Earlier studies have observed that ClO 2 has a potent antimicrobial activity against bacteria, fungi, protozoa, and viruses (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Although the disinfecting power of chlorine is well documented in the literature against all types of microbes including viruses, the detection of Rotaviruses in the drinking water sample in Shark El-Mansoura WTP suggested a failure in the chlorination process which needs attention. Chlorination was reported denature the proteins and causes breakage in the nucleic acid molecules (Ogata, 2007). These should be sufficient to remove all forms of microbes and viruses.…”
Section: Resultsmentioning
confidence: 99%